Kreativitas Guru dalam Memanfaatkan Infrastruktur Pembelajaran untuk Menciptakan Lingkungan Belajar Efektif di Kelas V SD Sukasari Cirebon - Zulfa Afifah Afra; Khoerunnisa Utami Putri Efendi; Suherli Kusmana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Effective learning in elementary schools requires not only curriculum and teacher competence, but also the teacher’s ability to creatively utilize available learning infrastructure. This study aims to: (1) describe the forms of teacher creativity in utilizing learning infrastructure in Class V of SD Sukasari Cirebon; (2) analyze how the utilization of infrastructure supports the creation of an effective learning environment; and (3) identify supporting and inhibiting factors of teacher creativity in managing learning facilities. This research uses a qualitative descriptive approach. Data were collected through in-depth interviews with Class V teachers, the school principal, and students, direct observation of learning processes, and documentation of classroom facilities, learning media, and school documents. Data were analyzed using Miles and Huberman’s interactive model consisting of data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technical triangulation. The findings reveal that Class V teachers at SD Sukasari creatively utilize digital learning panels (PID/digitalization boards), infocus projectors, and self-made teaching aids to create an engaging learning environment. Teacher creativity significantly enhances student motivation, active participation, and comprehension of learning materials, a finding corroborated directly by students themselves. Supporting factors include availability of digital infrastructure, school principal support including digital-competency training, and student enthusiasm, while inhibiting factors include limited PID units requiring schedule rotation, time constraints for preparation, and the multilayered administrative duties of teachers. This study concludes that teacher creativity in maximizing existing learning infrastructure is a key determinant in creating an effective learning environment in elementary schools.